The Effect of Rewards and Work Discipline on Employee Performances - Puti Harissa Pratidhina; Budhi Satriawan; Andriana Andriana; Maria Suryaningsih (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
Owned high-performance employees can make organizational goals achieved; otherwise, organizational goals cannot be achieved if employees do not have performance in carrying out tasks by the responsibilities given. The factors that can affect performance are rewards and discipline. The purpose of this study was to determine the effect of reward and work discipline on employee performance. The method used in this research is a literature review study. The results obtained are from 10 journals that are included in the inclusion criteria, the majority have results where rewards and work discipline have a significant positive influence. The conclusion that can be drawn from this research is that rewards and work discipline can have a positive influence on employee performance.